(untitled) (Journal of actual problems of jurisprudence, 2018)
Under the Law of РК ст 1046. Will of citizen confesses a testament at the direction belonging to him property in case of death. A testament is accomplished by a citizen possessing in the moment of his feasance a capability in full.A citizen can bequeath all property or part of him one or to a few persons, as entering, so not included in the circle of heir-at-laws, and also to the legal entities and state. A testament must be accomplished personally. The feasance of testament through a representative is shut out. Testament with a condition Testator is right to stipulate the receipt of inheritance a certain condition in relation to the pattern of behaviour of heir. The terms plugged in an order about setting of heir or privation of succession of rights are invalid. The terms that is unexecutable for a heir on the state his health or by virtue of another objective reasons plugged in a testament can be confessed by invalid on a lawsuit a heir. Keywords: Testament with a condition, accomplished, The terms that is unexecutable for.